2009
DOI: 10.1080/00036840601007393
|View full text |Cite
|
Sign up to set email alerts
|

Evidence on economic growth and government size

Abstract: The purpose of this article is to explore the effect of government size on economic growth in the United States using time-series data over the period 1950 to 1998. A multi-equation model is developed to examine the relationship between economic growth and government size. The results indicate that government size has a significant and negative effect on economic growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…However, the variations in labor and oil price are never significant. The absence of an effect of the labor variable is not an unusual result in the literature (see, e.g., Roy 2009). Also, it is unlikely that oil prices affected French economic growth before World War II, which explains their lack of significance.…”
Section: A Ideology and Economic Growthmentioning
confidence: 78%
“…However, the variations in labor and oil price are never significant. The absence of an effect of the labor variable is not an unusual result in the literature (see, e.g., Roy 2009). Also, it is unlikely that oil prices affected French economic growth before World War II, which explains their lack of significance.…”
Section: A Ideology and Economic Growthmentioning
confidence: 78%
“…Several other studies such as Karras (1996Karras ( , 1997, Guseh (1997), Aly and Strazicich (2000), Folster and Henrekson (2001), Alleyne et al (2004), Romero-Avila andStrauch (2008), Roy (2009), Afonso and Fuceri (2010) mentioned that public spending had a significant negative impact while other studies such as Ram (1986), Ghali (1999), Gunalp and Gur (2002), Alexiou (2009) and Gunalp and Dinçer ( 2010) depicted a positive one. Armey (1995) proposed an inverted U-shaped curve to study the effect of public spending on economic growth.…”
Section: Section 1: Effect Of Public Expenditure On Growth-positive Negative and Insignificantmentioning
confidence: 97%
“…The effect of government size on economic growth has become one of the frequently addressed issues in the debates and the relation between government expenditures and economic growth has been examined in the positive, negative and nonlinear direction. The studies by [7]- [18] found statistically significant negative relations between government size and economic growth.…”
Section: Literature Reviewmentioning
confidence: 96%